Etude de l’effet de réchauffement par micro-ondes sur la qualité physico-chimique et organoleptique du lait cru et du lait pasteurisé conditionné - BENYEKKOU, Nassima; MOHAMED BEN ATTIA, Nadjette (My University, 2020)
Milk and dairy products are the most popular foods around the world especially for infants more recently and almost most use microwaves in the preparation of food especially milk. Thus, the objective of this study aims to see the effect of microwave heating on the physicochemical and organoleptic quality of milk heated at different intervals as a function of time (20secs « 36°C », 30secs « 41°C » and 40secs « 46 °C ») and for this, We have chosen raw milk and packaged pasteurized milk which are considered to be the most used for milk production intended for human consumption. The results obtained showed that the fat content and the density decreased for both types of milk especially after 40 seconds of heating in the microwave, for raw milk there is a decrease of (35.5 to 34.5 g/L) in fat and (1033 to 1028.5) in density, for packaged pasteurized milk there is a decrease of (15.5 to 14.9 g / L) in fat and (1032.5 to 1028.5) in density unlike the acidity which has increased (17 at 18.5 °D) for raw milk and (16 to 17.5 °D) for packaged pasteurized milk. For the sensory evaluation, the results obtained during this study indicate that the sensory profiles of the majority of milks are different and we note the increase in the intensity of certain descriptors such as the taste of fat for the two types of milk, and the decrease in other descriptors including the color yellow and medium white. We conclude that the physicochemical parameters are sensitive indicators of the quality of milk and we can also say that heating changes the organoleptic characteristics of milk.
Keywords: raw milk; packaged pasteurized milk; microwave; physic-chemical quality; arganoleptic quality